A multi-dimensional modified deep learning framework for predicting potential creep-type landslides based on geological data - Yue Liu; Peihua Xu; Chen Cao; Liling Jin; Bo Han; Rongchen Ma; Chensi Li (Earth Science Informatics, 2026)

Beyond Single Stressors: Integrated Physiological and Transcriptomic Responses of Argopecten irradians Exposed to Polystyrene and Toxic Dinoflagellates - Weijia Song; Jianguo Ding; Liling Guan; Jie Ma; Huixuan Liu; Hongli Zhang; Yangjun Chen; Kaiqin Jiang (Oceans, 2026)
Toxic dinoflagellate blooms and microplastics are widespread coastal pollutants. In this study, the scallop, Argopecten irradians, was selected as an experimental organism to systematically investigate the single and combined toxic effects of polystyrene (PS) and the toxic dinoflagellate, Alexandrium pacificum. The results showed that both PS and algal cells could be ingested by A. irradians. The survival rate of A. irradians remained above 90% in both the single and combined treatment groups, indicating that 1 mg/L PS and 1500 cells/mL A. pacificum cells did not pose a serious threat to scallop survival in the short term. However, CAT, SOD, and GSH-ST activities, as well as MDA content, were all elevated in the combined treatment group. Transcriptomic analysis further revealed that A. pacificum primarily affected immune-related pathways, whereas PS might interfere with endocrine function through the release of additives. Combined exposure to PS and A. pacificum induced more complex synergistic effects, reflected in the metabolic stress of exogenous substances, and the disruption of developmental and homeostasis regulatory pathways. This study provides important theoretical support for assessing the threats posed by composite coastal pollution to aquaculture and marine ecological security.

Uncovering the potential effect of microplastics on Alexandrium pacificum: From the perspective of cyst formation and toxin production - Weijia Song; Peipei Zhang; Jianguo Ding; Jie Ma; Hongli Zhang; Liling Guan; Zhihua Feng (Marine Environmental Research, 2026)

The role and regulation of SIRT1 in pulmonary fibrosis - Xinyi Ma; Mengna Jiang; Wenqian Ji; Mengjiao Yu; Can Tang; Kai Tian; Zhengnan Gao; Liling Su; Juan Tang; Xinyuan Zhao (Molecular Biology Reports, 2024)

Associations between metal(loid) exposure with overweight and obesity and abdominal obesity in the general population: A cross-sectional study in China - Tianran Shen; Liling Zhong; Guiyuan Ji; Baolan Chen; Mengfan Liao; Lvrong Li; Huiming Huang; Jiajie Li; Yuan Wei; Shan Wu; Zihui Chen; Wenjun Ma; et al. (Chemosphere, 2024)

Nanocellulose-enhanced smart film for the accurate monitoring of shrimp freshness via anthocyanin-induced color changes - Liling Li; Wenxiu Wang; Mengdan Zheng; Jianfeng Sun; Zhizhou Chen; Jie Wang; Qianyun Ma (Carbohydrate Polymers, 2023)

Tumor suppressor LHPP suppresses cell proliferation and epithelial-mesenchymal transition in hepatocellular carcinoma cell lines - Lunkun Ma; Huifang Sun; Xichao Xu; Ying Chen; Lu Zhang; Shun Li; Liling Tang (Journal of Physiology and Biochemistry, 2022)

Genetic and biological characteristics of the globally circulating H5N8 avian influenza viruses and the protective efficacy offered by the poultry vaccine currently used in China - Pengfei Cui; Xianying Zeng; Xuyong Li; Yanbing Li; Jianzhong Shi; Conghui Zhao; Zhiyuan Qu; Yanwen Wang; Jing Guo; Wenli Gu; Qi Ma; Yuancheng Zhang; et al. (Science China Life Sciences, 2022)
The H5N8 avian influenza viruses have been widely circulating in wild birds and are responsible for the loss of over 33 million domestic poultry in Europe, Russia, Middle East, and Asia since January 2020. To monitor the invasion and spread of the H5N8 virus in China, we performed active surveillance by analyzing 317 wild bird samples and swab samples collected from 41,172 poultry all over the country. We isolated 22 H5N8 viruses from wild birds and 14 H5N8 viruses from waterfowls. Genetic analysis indicated that the 36 viruses formed two different genotypes: one genotype viruses were widely detected from different wild birds and domestic waterfowls; the other genotype was isolated from a whopper swan. We further revealed the origin and spatiotemporal spread of these two distinct H5N8 virus genotypes in 2020 and 2021. Animal studies indicated that the H5N8 isolates are highly pathogenic to chickens, mildly pathogenic in ducks, but have distinct pathotypes in mice. Moreover, we found that vaccinated poultry in China could be completely protected against H5N8 virus challenge. Given that the H5N8 viruses are likely to continue to spread in wild birds, vaccination of poultry is highly recommended in high-risk countries to prevent H5N8 avian influenza.

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Prefabrication of axially vascularized bone by combining β-tricalciumphosphate, arteriovenous loop, and cell sheet technique - Dongyang Ma; Liling Ren; Zhen Cao; Jianxue Li; Jian Cao; Wenyan Tian; Hong Yao (Tissue Engineering and Regenerative Medicine, 2016)

Development of an indirect competitive enzyme-linked immunosorbent assay (icELISA) using highly specific monoclonal antibody against paclitaxel - Zhi Chao; Mingming Tan; Madan Kumar Paudel; Seiichi Sakamoto; Liling Ma; Kaori Sasaki-Tabata; Hiroyuki Tanaka; Yukihiro Shoyama; Lijiang Xuan; Satoshi Morimoto (Journal of Natural Medicines, 2013)